2021
DOI: 10.12659/msm.930241
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Immunodeficiency and Hypogammaglobulinemia with IgG Levels of <5 g/L in Patients with Multiple Myeloma: A Retrospective Study Between 2012 and 2020 at a University Hospital in China

Abstract: Background Infections are the main cause of mortality and morbidity in multiple myeloma (MM) patients. However, adult immunodeficiency specialists in China are lacking, and the care of secondary immunodeficiency (SID) and the prognostic role of hypogammaglobulinemia in MM is unknown. Material/Methods MM patients (295) were retrospectively analyzed between January 2012 and 2020 in Zhejiang Provincial People’s Hospital, Hangzhou Medical College. MM patients with immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A total of 43 articles relevant to the topic of IgRT in HMs were identified within the period of 2012-2022. Of these articles, 4 were qualitative studies, 12,27-29 10 were narrative literature syntheses which featured expert opinions, 17,[30][31][32][33][34][35][36][37][38] 1 was a systematic review, 39 15 were retrospective casecontrolled cohort studies, [40][41][42][43][44][45][46][47][48][49][50][51][52][53]67 1 was a non-randomised control trial, 54 1 was a mixed-methods cohort study, 55 4 were case reports, [56][57][58][59] 6 were prospective case-controlled studies [60][61][62][63][64][65] and 1 was a randomised placebo-controlled trial 66 (Figure 2). On first glance, it could be argued that these data demonstrate a lack of rigour in the studies conducted; however, in reality, the study of medicine use and access is often best investigated using cohort studies as they provide a realistic source of data and are more costeffective and cause less disruption to healthcare provision than randomised control trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 43 articles relevant to the topic of IgRT in HMs were identified within the period of 2012-2022. Of these articles, 4 were qualitative studies, 12,27-29 10 were narrative literature syntheses which featured expert opinions, 17,[30][31][32][33][34][35][36][37][38] 1 was a systematic review, 39 15 were retrospective casecontrolled cohort studies, [40][41][42][43][44][45][46][47][48][49][50][51][52][53]67 1 was a non-randomised control trial, 54 1 was a mixed-methods cohort study, 55 4 were case reports, [56][57][58][59] 6 were prospective case-controlled studies [60][61][62][63][64][65] and 1 was a randomised placebo-controlled trial 66 (Figure 2). On first glance, it could be argued that these data demonstrate a lack of rigour in the studies conducted; however, in reality, the study of medicine use and access is often best investigated using cohort studies as they provide a realistic source of data and are more costeffective and cause less disruption to healthcare provision than randomised control trials.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, now is the time to invest resources into addressing the topic of immunoglobulin use, so that patients can continue to access IgRT as a supportive cancer treatment in HM. Geographical location: China (n = 2), 27,46 France (n = 3), 34,48,64 Oceania -Australia/New Zealand (n = 2), 29,40 United States (n = 7), 43,45,[52][53][54]58,63 Italy (n = 7), 33,41,47,49,50,66,67 Sweden (n = 1), 55 Japan (n = 1), 56 Spain (n = 2), 35,42 United Kingdom (n = 2), 44,61 Germany (n = 2), 60,62 Belgium (n = 1), 37 Greece (n = 1) 51 and India (n = 1). 65…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Moreover, hyper/hypogammaglobulinemia, hypercalcemia, and amyloidosis are the most common causes of the development of renal insufficiency in MM 18 . Also, immune deficiency in MM increases the risk for secondary bacterial infections 19 …”
Section: MMmentioning
confidence: 99%
“…The median survival time was considerably shorter in MM subjects with SID (24 vs 66 months). More importantly, the multivariate and univariate analysis revealed that IgG <5 g/L was an independent prognostic factor for MM patients ( 80 ).…”
Section: Characteristics Of Secondary Immunodeficiency In Patients With Multiple Myelomamentioning
confidence: 99%